Education expansion and income inequality: Empirical evidence from China - Xiaoshan Hu; Guanghua Wan; Congmin Zuo (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
Education has long been perceived as a great equalizer, but even with universal rises in schooling years, income distribution worsened world-wide. We propose a method for decomposing the contribution of a variable to the change in inequality into mean, dispersion, and price components. The proposed method is then used to investigate the roles of the education variable in driving down China's wage inequality between 2010 and 2018. We find that (1) education accounted for over 30% of total wage inequality in 2010 and 2018; (2) 70% of the overall decline in wage inequality from 2010 to 2018 can be attributed to education expansion, and (3) the 70% inequality-reducing effect was made up of 95% benign dispersion and price components and 25% malign mean component. The benign components are attributable to an improvement in educational equity and a decrease in the college premium.
urn:nbn:fi-fe20231204151157
Keywords: I24; I26; J31; 330; Education Expansion; Wage Inequality; Rate of Return to Education; China